Upward flow type biological aerated filter - CAO WEN; ZHU RONG; DONG QIANG; HU FANGMEI; LIU DONGWEI; LIU CUN; XIAO ZHONGXING (2015)
The utility model relates to an upward flow type biological aerated filter. The biological aerated filter comprises a plurality of filter bodies sequentially connected in series; each filter body is provided with a water feed area, sewage enters the water feed area at the bottom of the first filter body through a pipeline, and each water feed area is further connected with a sludge discharge pipe; a filtering area is arranged on the water feed area of each filter body, each filtering area is filled with ceramisite filter materials, a supporting partition plate is arranged on the lower side of each filtering area, each partition plate is fixedly provided with filtering heads, and an aerator pipe is further arranged on the lower sides of the filter materials; except the first filter body, an overflowing weir is arranged on the top of the side, close to the former filter body, of each filter body, the water feed area and the overflowing weir of each filter body are connected through a water delivery pipe, and the heights of the overflowing weirs of all the filter bodies gradually decrease from the water feed end to the water discharge end of the biological aerated filter. The upward flow type biological aerated filter is easy to maintain and not prone to blockage and effectively improves the flushing effect on sewage.